La transformación de la contratación laboral, el trabajo a tiempo parcial y el despido - Lahera Forteza, Jesús; García Quiñones, Juan Carlos (Cuadernos de Relaciones Laborales, 2008)
Temporary employment, part time employment and the extinction of employment contrats are aspects which have been importantly changed in Spanish Labour Law. The aim of this paper is to explain this changes, that affect to the basis of the employment relationship. With this purpose it is done in each theme a short historic view of the legal evolution and the currently regulation is explained, showing the esential points of the transformation, resumed in the promotion of temporary employment, flexibility and individualitation of part time work, the debilitation of causes required for dismissal and lower costs for cancelling employment contract. The evolution and current regulation of temporary employment, the part time work and the dismissal is influenced by the labour flexibility, in such a way that this study has also as a purpose the importance of flexibility in the basic structures of the employment relationships.
Keywords: Labour Flexibility; Precarious employment; Flexible part time work; Free-paid-dismissal